Performance Enhancement of MoSe2 and WSe2 Based Junction Field Effect Transistors with Gate-All-Around Structure - Changlim Woo; Abdelkader Abderrahmane; Pangum Jung; Pilju Ko (Crystals)
Recently, two-dimensional materials have gained significant attention due to their outstanding properties such as high charge mobility, mechanical strength, and electrical characteristics. These materials are considered one of the most promising solutions to overcome the limitations of semiconductor technology and are being utilized in various semiconductor device research. In particular, molybdenum diselenide (MoSe2) and tungsten diselenide (WSe2) are actively being developed for device applications due to their high electron mobility, optical properties, and electrical characteristics. In this study, we fabricated MoSe2 and WSe2-based junction field-effect transistors (JFET) and further deposited two-dimensional materials on the same device to fabricate and compare JFETs with a gate-all-around (GAA) structure. The research results showed that the GAA-structure JFET exhibited performance improvements in drain current, subthreshold swing (SS) transconductance (gm), and mobility, achieving enhancements ranging from a minimum of 1.2 times to a maximum of 10 times compared to conventional JFET.